DEVELOPING A CONTEXTUAL LEARNING-BASED AUDIO VISUAL MEDIA ON MATERIAL OF THE ENERGY SOURCE AND ITS CHANGE FOR FOUR GRADE STUDENTS AT ELEMENTARY SCHOOLS - Maulina Agustini; Lukman Nulhakim; Zerri Rahman Hakim (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to develop a contextual learning–based audiovisual media and examine its validity. This study utilized the Research and Development (R&D) method, referring to Borg and Gall’s development model which consisted of six stages: (1) problem analysis, (2) data collection, (3) product design, (4) validation, (5) product revision, and (6) product trial testing. The study was conducted on fourth-grade students at SD Negeri Salatuhur. Based on the validity examined by the experts—media expert, language expert, and material expert—the average score of the validity from the media expert was 92% in the very feasible category. The average validity score from the material expert was 85.49% in the very feasible category. Meanwhile, the average validity score from the language expert was 94.16%, also in the very feasible category. Moreover, the results of students’ responses obtained a score of 97.49% in the very feasible category. Based on the research results, the final product of a contextual learning–based audiovisual media on the material of energy sources and their changes was feasible to be utilized for learning activities of fourth-grade elementary school students.